Controlling the length of porphyrin supramolecular polymers via coupled equilibria and dilution-induced supramolecular polymerization - Elisabeth Weyandt; Luigi Leanza; Riccardo Capelli; Giovanni M. Pavan; Ghislaine Vantomme; E. W. Meijer (Nature Communications, 2022)
Controlling multicomponent systems is difficult due to convoluted behavior, pathway complexity, and coupled equilibria. Here the authors showed modulation of aggregate morphology in a zinc porphyrin-based supramolecular system via judicious capping with a manganese porphyrin monomer, in which the monomer’s chirality can influence the supramolecular behavior.